Lecturers’ Individual Factors of Knowledge-sharing Behavior: A Study in Islamic Higher Education Institutions - Suhra Wardi; Mardi Widodo; Asri Ady Bakri (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to analyze lecturers' knowledge-sharing behavior at Indonesian Islamic universities. Knowledge-sharing behavior is reviewed based on individual attitude factors and individual expectations, which are developed into six question items that have been qualitatively validated by experts. This research was conducted on lecturers at Islamic-based tertiary institutions in Indonesia. Data were collected using survey techniques with the help of Google Forms. The data were analyzed using the frequency and percentage tabulation approaches. The results of the data analysis show that lecturers have an individual attitude factor of 86.1% and a personal expectation factor of 78.2%. As an implication, knowledge-sharing behavior can be increased through individual attitude factors such as awareness of increasing and developing knowledge and as a contribution to the institution.